Plasma amino acid levels in individuals with bacterial pneumonia and healthy controls. (August 2021) - Ikeda, Hideki
Summary: Background & aims: Amino acids play an important role in immune responses and as neurotransmitters. During the course of a bacterial pneumonia episode, from the onset to the recovery phase, immune responses dramatically change, as does the metabolism of amino acids, a concept referred to as immuno-nutrition. We investigated the differences in plasma amino acid levels (PAA) between the acute and recovery phases in individuals with community-acquired pneumonia (CAP) and healthy controls. Methods: Two groups of participants were recruited: Healthy adults aged over 60 years and patients hospitalized with CAP. Samples were collected on Day 0 (the day of admission) and Day 7 (after 6–8 days treatment). Results: A total of 93 healthy adults and 60 patients with CAP participated in the study. Of those with CAP, 43 had their amino acids measured on Day 7. Patients with CAP had markedly decreased PAA of 12 amino acids on Day 0. Citrulline, histidine, and tryptophan remained low in male, while aspartic acid, asparagine, ornithine, proline, and threonine were higher on Day 7 in both males and females. Phenylalanine increased at Day 0 and Day7. Conclusions: The findings suggest that the host response against bacterial infection changed the plasma amino acid levels. PAA on Day 7 (representing convalescence) continued to display an amino acid profile distinct from that observed in healthy individuals. Based on these findings, reconsideration for providing amino acids to patients with bacterial pneumonia should be needed depending on stage of the pneumonia from the perspective of immuno-nutrition.